Determinants of table tennis performance in elite Scottish youth players using a multidimensional approach: a pilot study - Doherty, S.; Martinent, G.; Martindale, A.; Faber, I. (Proceedings Book of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017, 2017)
Fourteen elite Scottish youth male table tennis players were assessed using a multidimensional profiling model in order to identify determinants of performance. Data on anthropometrics for maturation, perceptuo-motor and psychological skills as well as each players` training history were gathered. Spearman correlation coefficient between the determinants and performance outcomes were calculated. A significant correlation (R = -0.73, P = .001) between the age to peak height velocity (APHV) and progression scores (rating 2017 minus rating 2016) was revealed, suggesting that a player pre-APHV was likely to improve their rating by more points than a player post-APHV. This might be explained by the physical maturation an individual experiences, which is supported by the significant correlations found between height (R = -0.72, P = .004), weight (R = -0.56, P = .039) and the sprint test (R= .63, P = .017) with the progression scores. Moreover there was a significant correlation between the number of playing years and the rating in both (2016: R = .84, P < .001; 2017: R = .79, P = .001). Analysis also suggested a younger starting age benefited ratings, with a significant correlation found between starting age and the 2017 ratings (R = -0.72, P = .003). A player will have had more time to practice the longer they have been playing, allowing more time for skill development, competition experience and physical training. Furthermore, as this study included players ranging in ages from 13-17, the players who had been playing for longer were also likely to be older and subsequently more physically mature.